The effect of substrate and enzyme concentration to the fructooligosaccharides (FOS) production - Rodianah, Alias (2009)
The fructooligosaccharides (FOS) are oligosaccharides of fructose that have simple molecule. They can produced by action of fructosyltransferase with sucrose. The fructooligosaccharides is significant to the diabetec and colon disease due to its function reducing the content of sugar in blood. FOS also has a function of prebiotic whereas capable help in human digestion colon. The purpose of this research to determine the effect of substrate and enzyme and the optimum both two of these factor to produce FOS The experiment is carried out used 40 to 80% (w/v) of sucrose concentration and 5% to 9% (w/v) of enzyme concentration in water bath at temperature of 60 °C at 100 rpm. The samples were analyzed by using HPLC, UV-Vis, and TOC to determine FOS concentration, sucrose residual and TOC content respectively. The Design Expert Software also involve to determine the optimum substrate and enzyme to produce FOS. From the result acquire, Increased 40 to 60% of sucrose concentration resulted in increased 96% FOS production and constant after 60% of sucrose concentration approximately at 258 mg/ml. As increasing of enzyme concentration, the production of FOS also increase up to the maximum point of 241 mg/ml FOS production at 5% to 7% enzyme concentration and decrease after 7% enzyme concentration to 134 mg/ml. By using Design Expert Software, increased of sucrose concentration, the FOS production also increase. Increased of enzyme concentration, the FOS production also increase. The optimum condition of substrate and enzyme concentration is 50% and 7% to produce 552.857 mg/ml concentration of FOS. -Author-